Perancangan Sistem Kehadiran Face Recognition Menggunakan Mikrokomputer Berbasis Internet of Things - Roihan, Ahmad; Rahayu, Nina; Aji, Danang Saputro (Technomedia Journal, 2021)
All companies want a better attendance system which can increase the level of employee discipline in attendance. In this case, a problem must be sought for a solution and requires facilities or design in the form of a presence system that can facilitate attendance and reduce the occurrence of errors and fraud. This research develops the system as a solution to the problem of the presence system that already exists today with the presence system with face recognition. Raspberry Pi is used as a microcomputer to perform data processing to activate a webcam that will detect faces when motion has been detected by the PIR sensor as input and design using the Python programming language that is run on the Raspbian operating system platform. The purpose of this study is to be able to implement a system that can read employee faces to input attendance in real time. Keywords: Presence, Raspberry, Face Recognition, Webcam, Python